2017
DOI: 10.1177/2045125317707746
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced hypersalivation: the association between quantification, perceived burden and treatment satisfaction reported by patients

Abstract: We read with great interest the recent Therapeutic Advances in Psychopharmacology article by Maher and colleagues entitled 'Clozapine-induced hypersalivation: an estimate of prevalence, severity and impact on quality of life'. 1 The authors evaluated the prevalence of clozapine-induced hypersalivation (CIH) in a population of psychiatric patients in a specialized clozapine clinic. In addition, they assessed and quantified the severity of CIH, using the Nocturnal Hypersalivation Rating Scale (NHRS) and the Droo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Of the total 48 studies on patient perspectives, 16 reported on perspectives belonging to schizophrenia patients in specific 29 30 35 37 39 43 58 63 65 70 71 7578 84 , two on non-schizophrenia patients only 67 74 , 18 on patients of mixed diagnoses 2325 34 36 38 41 42 57 6062 68 69 72 73 79 82 and in 12 studies 22 3133 56 59 64 66 80 81 85 193 the type of patients was unclear (Figure 2, row 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the total 48 studies on patient perspectives, 16 reported on perspectives belonging to schizophrenia patients in specific 29 30 35 37 39 43 58 63 65 70 71 7578 84 , two on non-schizophrenia patients only 67 74 , 18 on patients of mixed diagnoses 2325 34 36 38 41 42 57 6062 68 69 72 73 79 82 and in 12 studies 22 3133 56 59 64 66 80 81 85 193 the type of patients was unclear (Figure 2, row 1).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the management of adverse events of already approved antipsychotics in schizophrenia, glycopyrrolate (a mus carinic receptor antagonist) improved sial orrhea more than placebo in a phase 2 trial (EU201200229915) 69 .…”
Section: Schizophreniamentioning
confidence: 99%